The three Billy Goats Fluff - Mortimer, Rachael (Tiger Tales, 2011)
In this retelling of the classic fable, how is Mr. Troll supposed to sleep when the three Billy Goats Fluff travel noisily over his bridge every day? The goats go to a field that makes their fleece extra fluffy for Mother Goat's knitting business. One day Mr. Troll loses his temper and threatens to eat the Fluffs. How will Mother Goat solve the problem and make a friend of Mr. Troll?